(untitled) (Transactions of the Association of European Schools of Planning, 2020)
The ambitions of the European Spatial Development Perspective (ESDP) in relation to the development of European Union space seem to have been dissolved in the notion of territory which has become a key word in EU Cohesion Policy. The term ‘territory’ has been the subject of many debates, from attempts at definitions, to its rejection as a marker of a renunciation of the aspiration to reflect on, and adjust, development to spatial realities. Based on a constructivist definition of the concept of territory, this article argues that it is not possible to separate territory as a ‘container’ from the various realities of space in so far as the two dimensions are closely intertwined. Furthermore, it could be useful to consider these two dimensions in analysing EU space when reflecting on spatial planning at this scale.